PRODUKSI GETAH PINUS (Pinus merkusii Jung et de Vriese) PADA BERBAGAI DIAMETER BATANG MENGGUNAKAN SISTEM KOAKAN DI DESA NAMO KECAMATAN KULAWI KABUPATEN SIGI - Mampi, Budiman; Hapid, Abdul; Mutmainnah, . (Jurnal Warta Rimba, 2018)
Pine trees (Pinus merkusii Jung et de Vresie) are one type of plant that is widely used in reforestation and industrial plantations. In addition, Pine is also one of the types of forest plants that have multiple benefits because in addition to producing wood it also produces sap that can produce gonderukem and turpentine. Utilization of non-timber forest products, especially tapping pine resin in Namo Village has not been done optimally. To find out how much the production of pine sap is produced with certainty, a research is conducted on the amount of pine tapping production in Namo Village, Kulawi District, Sigi Regency. The research was conducted for 3 months, from November 2015 to February 2016. The study site was located in Namo Village, Kulawi District, Sigi Regency, Central Sulawesi Province. This study used a completely randomized design (CRD) with 4 treatments, namely: (a) Class diameter I = 60-70 cm, (b) Class diameter II = 70-80 cm, (c) Class diameter III = 80-90 cm, (d) IV diameter class = 90-100 cm with 5 replications. The research data was analyzed by variance. The results showed that the value of pine sap production (Pinus merkusii Jung et de Vriese) in IV diameter class (90-100 cm) was 37.882 gr / tree / 7 days, diameter III class (80-90 cm) was 35.602 gr / tree / 7 days, diameter II class (70-80 cm) is 31,934 gr / tree / 7 days and class diameter I (60-70 cm) is 28.84 gr / tree / 7 days. From these results, the treatment of IV diameter classes is significantly different from the treatment of diameter classes III, II, and I.Keywords: Production of Pine Gum, Diameter Class, Koakan